Effects of Lower-Body Muscular Fatigue on Vertical Jump and Balance Performance. Issue 10 (October 2020) - Cooper, Christina N.; Dabbs, Nicole C.; Davis, Judith; Sauls, Nicole M.
Abstract : Abstract: Cooper, CN, Dabbs, NC, Davis, J, and Sauls, NM. Effects of lower-body muscular fatigue on vertical jump and balance performance. J Strength Cond Res 34(10): 2903–2910, 2020—Lower-body fatigue can lead to a decline in vertical jump (VJ) and balance performance due to decreased motor control and coordination. The purpose is to determine the effects of lower-body fatigue on VJ and balance performance. Twenty-four recreationally trained individuals participated in a single 1-hour familiarization and testing session. Participants were familiarized with balance, countermovement vertical jump (CMVJ), and static vertical jump (SVJ) using the Vertec. Three trials of static and dynamic balance tests were completed. Three trials of a SVJ and CMVJ were completed in a randomized order pre/post fatigue protocol. Three trials of double-leg and single-leg tests were performed. Dependent t tests analyzed differences between pre/post fatigue protocol for jumping and balance measures. There was a significant ( p < 0.001) difference between pre/post measures for SVJ-H (height), CMVJ-H, and CMVJ peak power (PP). Results showed an interaction ( p < 0.05) for group by time for CMVJ-H, CMVJ-peak force (PF), SVJ-PF, and SVJ-PP. There were no main effects ( p > 0.05) for time or group for SVJ-rate of velocity development and SVJ-impact force (IF). There were no interactions, time effects, and group effects for balance variables ( p > 0.05). Bosco protocol decreased VJ height and PF in SVJ, and VJ height and PF, IF, peak velocity, and PP for CMVJ potentially due to decreased muscle control, coordination, and force-generating capacity after fatigue. Practitioners should consider fatiguing effects on individuals performing jumping motions but it seems that fatigue has no effect on balance.